Injection Effects on Sediment Transport in Closed-Conduit Flows - Cao, Deping (2016)
Experiments were conducted to investigate injection effects on sediment transport in closed-conduit flows. The results show that the sediment transport rate essentially remains unchanged when the ratio of the injection velocity and that at boiling, Vi/Vcr < 10. However, significant sediment transport rate is observed when Vi/Vcr increases beyond this limit. In the literature, three semi-empirical models have been developed to relate seepage effects on the sediment transport rate. The experimentally measured data in the pre- and post-boiling condition (Liu and Chiew 2014, and the present study, respectively) are compared with these models. The results show that the models of Francalanci et al. (2008) and Nielsen et al. (2001) perform poorly in predicting injection effects on the sediment transport. Although Yang’s (2013) model could reasonably predict the influence of injection on the sediment transport rate in the post-boiling condition, it similarly fails when applied to the pre-boiling condition.